PERAN BUDAYA LOKAL DALAM PEMBENTUKAN SAINS: Studi Naturalistik Pembentukan Sains Siswa Kelompok Budaya Sunda Tentang Fotosintesis dan Respirasi Tumbuhan Dalam Konteks Sekolah Dan Lingkungan Pertanian - Djulia, Ely (2005)
naturalistic study on the context of school classroom and indigenous learning in agricultural environment, had been conducted in West Java and Banten provinces to investigate the science acquisition on Sundanese High School students of photosynthesis and plant respiration. Three kinds of test including concept mapping, conceptual change, and concomitant concepts test were administered towards Senior High Schools science students. Observation and interview were conducted towards some key informants at traditional community. This analytic-descriptive study resulted in various level of understanding on students' conception of photosynthesis and plant respiration. There are misconception, partial, and scientific understanding which included concept-process-context understanding, physiology, anatomy, and chemical understanding. It was found that there were three pattern of integrating community (A) and school (B) science, i.e. (A<B = 39,5%), (A>B = 33,4%), and (A = B = 27,1%). These patterns showed dynamic continuum on three dimension. First dimension is science acquisition on vertical direction that get along by second dimension of scientific conception. Both of them distributed on the third dimension of the sequence of concepts of community and school science on horizontal direction. The tendency of science acquisition on students who practice directly in farming with their parents, the increase of science achievement get along by the tendency of community science (A), school science (B) into the balance of the two (A=B). While those who didn't practice directly in farming anymore, the increase of learning achievement get along by the tendency of school science (B), community science (A) into the balance of the two (A=B). The tendency of integration of the two knowledge systems play an important role on science acquisition and information processing in long term memory, achieving the balance of science literacy dimension (concept, process, context) and developing ecological wisdom into nature.